Physical Plasticity of the Brain and Deep Brain Stimulation Lead: Evolution in the First Post-operative Week - Martino, Anthony; Darbin, Olivier; Templeton, Kelsey; Dees, Daniel; Lammle, Markus; Torres, Tatiana; Williams, Dakota; Naritoku, Dean (Frontiers in Surgery, 2020)
Background: Deep brain stimulation (DBS) is a therapy for movement disorders and psychiatric conditions. In the peri-operative period, brain shift occurs as the consequence of events related to the brain surgery which results in post-operative lead deformation. Objective: To quantify postoperative 3-dimensional DBS lead deformation after implantation. Methods: In 13 patients who had DBS lead implantation, we performed preoperative magnetic resonance imaging (MRI), preoperative computed tomography (CT) scans after placement of fiducial markers, and postoperative CT scans immediately, 24 to 48 hours, and 7 days after implantation. The MRI scans were used to define brain orientation and merged with CT scans. Lead deviation was determined relative to a theoretical linear lead path defined by the skull entry and target lead tip points. Results: In the sagittal plane, we distinguished an initial period after surgery (<48h) characterized by a deviation of the lead toward the rostral direction and a late period (over one week) characterized by a lead deviation toward the caudal direction. In the coronal plane, there was higher probability of lead deviation in the lateral than medial direction. During 7 days after implantation, there was net movement of the center of the lead anteriorly, and the half of the lead close to the entry point moved medially. These deviations appeared normative since all patients included in this study had benefits from DBS therapy with total power of charged comparable to those described in literature. Conclusion: DBS lead deviation occurs during 7 days after implantation. The range of deviation described in this study was not associated to adverse clinical effects and may be considered normative. Future multicenter studies would be helpful to define guide lines on DBS lead deformation and its contribution to clinical outcome.